Demonstration Booklet, 2001 Grade 12, Reading and Writing. Field Test. - National Center for Education Statistics (ED), Washington, DC.; National Center for Education Statistics (ED), Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 2001)
This demonstration booklet illustrates the kinds of exercises or test questions and tasks used in the assessment of student achievement in reading and writing by the National Assessment of Educational Progress (NAEP). Each student will be asked to complete the background section and the cognitive sections for one subject, and the assessment will require about 90 minutes of a student's time. The booklet for grade 12 is divided into four sections: Part One contains the general background questionnaire that students will be asked to answer; Parts Two and Three contain descriptions of each field test, followed by the booklet directions and the background questionnaire that accompanies each subject; and Part Four (located on the back cover) presents information about the program's purpose and what procedures to follow to obtain access to NAEP questions for further review. Parts Two and Three of the booklet also contain questions about how specific subject matter is taught and the materials and resources the students use; students will also be asked such questions as their racial and ethnic background, parental education, and the number of educational materials in the home. (NKA)
Availability: National Center for Education Statistics, NAEP Released Exercises, 1990 K St., N.W., Washington, DC 20006. Tel: 800-283-6237 (Toll Free). For full text: http://nces.ed.gov/nationsreportcard.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Achievement; Field Tests; Grade 12.; High Schools; Literacy; National Competency Tests; Reading Achievement; Standardized Tests; Student Evaluation; Writing Achievement; National Assessment of Educational Progress; Guides, Non-Classroom.; Tests/Questionnaires.